(3YLGFH GdebOhQ aj fhGFH JjehQs - (3CMeO Hf eMeO Hf YHO Gddg Hf EHQGgje, CHheMeO , TgGH GdOjf , GdeYQha HGHf YQHTGg,J (B854 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ydi efhGd EQGOJg hJOHjQg JfSL ebGWY GdCehQ CeG HYO adeG cGf ai GdJhGQjN YHQI def GYJHQ s
(3BNQgG (B:s
(3Ke hOYGfi heG hbaG hChOYGfi Cdje GdaQbG hGfUQaG hfSCd SHMGfg hJYGdi Cf jUhf Yf GdRdd CbhGdfG hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B228s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(626(3L(B) s
Keywords: (3GdJGQjNs